Donor age as an independent predictor of inferior outcomes after haploidentical hematopoietic cell transplantation in acute myeloid leukemia. Study conducted on behalf of GETH-TC - Munárriz, Daniel; Pérez-López, Estefanía; Martín Rodríguez, Carlos; Luque, Marta; Esquirol, Albert; Calvo, Carmen Martín; Aparicio, Clara; Peña-Muñóz, Felipe; Heras Fernando, Inmaculada; Oiartzabal Ormtegi, Itziar; Sáez Marín, Adolfo Jesús; Fernández-Luis, Sara; et al. (Frontiers in Immunology, 2025)
This study evaluated the impact of donor age on clinical outcomes in 274 patients with acute myeloid leukemia (AML) haplo-HCT using PTCY-based prophylaxis. Median patient age was 53 years, with 42.6% classified as high-risk AML. The median donor age of 38 years; 31% were under 30. An optimal donor age cut-off of 30 years was identified through ROC analysis. Patients receiving grafts from younger donors (<30 years) showed lower rates of aGVHD grade II–IV (3.0% vs. 19.9%, p < 0.001) and grade III–IV (1.5% vs. 10.2%, p = 0.034), with no differences in cGVHD or relapse rates. Overall survival (OS) was higher in the younger donor group (2-year: 80.6% vs. 64.3%, p = 0.011), along by lower non-relapse mortality (NRM) (2-year: 11.1% vs. 23.2%, p = 0.031). Multivariate analysis confirmed donor age ≥30 years as an independent adverse factor for OS (HR: 1.88, p = 0.019) and NRM (HR: 2.06, p = 0.049), along with older recipient age, higher HCT-CI score, and high-risk AML. These findings suggest that younger donor age contributes to improved survival, primarily through reduced NRM and aGVHD, supporting prioritization of younger donors when multiple haploidentical options are available to optimize transplant outcomes.